Epitope-level analysis of cross-reactive human HLA antibodies against genetically modified swine leukocyte antigens in xenotransplantation - Cho, Sang-Ik; Yan, Ji-Jing; Kim, Beom Seok; Ko, Nayoung; Shim, Joohyun; Kim, Hyunil; Oh, Eun-Jee (Frontiers in Immunology, 2025)
IntroductionXenotransplantation using genetically modified pigs is a promising solution to organ shortages, particularly for highly sensitized patients with broad anti-HLA sensitization who lack compatible allografts. However, preformed human anti-HLA antibodies may cross-react with porcine SLA, posing a barrier for clinical application. This study aims to characterize the extent and specificity of cross-reactive antibody responses against genetically engineered pig PBMCs, particularly from quadruple knockout (QKO) pigs.MethodsWe evaluated antibody binding and cytotoxicity of 68 human sera stratified by HLA class I and II antibody profiles using flow cytometric crossmatch (FCXM), complement-dependent cytotoxicity (CDC) assays (CDC-NIH and CDC-AHG), antibody elution, and single antigen bead assays. Porcine PBMCs from wild-type and gene-edited pigs (GTKO, TKO, QKO) were used. High-resolution SLA epitope mapping was performed with antibody eluted from select sera followed by in silico sequence and structural analyses.ResultsHuman sera showed strong IgG and IgM binding to wild-type pig PBMCs, which was significantly reduced by RBC adsorption, whereas binding to QKO pig PBMCs lacking key glycan xenoantigens was minimal and unaffected by RBC adsorption. Sensitized human sera with both HLA class I and II antibodies demonstrated significantly elevated IgG binding to QKO pig PBMC T and B cells compared to antibody-negative sera (p < 0.05). CDC-AHG assays revealed increased cytotoxicity titers (≥1:8) in HLA antibody-positive sera versus negatives (p < 0.01). Antibody elution from five crossmatch-positive sera identified predominant class I eplets (62EE, 162GLS, 163LG, 163LS/G, 166ES, 199V) and class II DR epitopes (13SE, 37F, 47F, 70D, 70DA) that target SLA 4.5/6.7 haplotypes. In contrast, anti-HLA-DQ and -DP reactivity was limited post-elution. Structural modeling confirmed that these epitopes are conserved and surface-exposed in SLA alleles.ConclusionCross-reactive anti-SLA antibodies are common in highly sensitized human sera, driven by antibody specificity and epitope conservation. Despite glycan xenoantigen deletion, sensitized sera maintain IgG-mediated cross-reactivity and cytotoxicity against gene-edited pig cells. These findings highlight the need for detailed epitope-level analysis to refine immunologic risk assessment and recipient selection to reduce antibody-mediated rejection in clinical xenotransplantation.